Modelling of RC Beams Strengthened with TRM in Shear - Sakr, Mohamed A.; Sleemah, Ayman A.; Khalifa, Tarek M.; Ali, Mohamed (International Journal For Research In Mechanical & Civil Engineering, 2020)
Textile-reinforced mortar systems are composed of high-strength textiles that are embedded in mortar matrix. This paper presents a 2D non-linear finite element model (FEM). Moreover, a new model to simulate the de-bonding failure between TRM and the concrete substrate was developed. This model based on the experimentally-available bondslip data that are depended on the degree of surface roughness. The proposed model verified with literature. The comparison between numerical and experimental results demonstrated that the FEM is able to simulate the overall response and capture different failure modes with a good agreement. Furthermore, the validated FEM was used to investigate the effect of different parameters on the overall behavior of the strengthened RC simple beams. These parameters included mortar thickness, fiber type and number of TRM layers.